2022
DOI: 10.1002/tox.23615
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dichloro‐2‐propanol induced ferroptosis through Nrf2/ARE signaling pathway in hepatocytes

Abstract: 1,3-Dichloro-2-propanol (1,3-DCP) is a representative chloropropane environmental contaminant with multiple toxicities. Ferroptosis is a novel iron-dependent form of regulated cell death that is closely associated with the accumulation of lipid peroxides, Fe 2+ and reactive oxygen species (ROS). In this study, we found that 1,3-DCP could induce mouse liver injury via ferroptosis. Administrating of C57BL/6J mice with 12.5, 25, and 50 mg/kg 1,3-DCP for 4 weeks via oral gavage, the data showed that 1,3-DCP exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…CRC is one of the common malignancies in China, and results in high incidence and mortality 25 . Ferroptosis, a programmed cell death characterized by iron metabolism and ROS accumulation, was reported to be involved in the pathogenesis of many injury models, such as acute lung injury (ALI), 26 liver injury, 27 and neuronal injury 28 . In recent years, ferroptosis induction has been regarded as a promising therapeutic approach for various cancers, such as acute myeloid leukemia, 29 nasopharyngeal carcinoma, 30 gastric cancer, 31 and breast cancer 32 .…”
Section: Discussionmentioning
confidence: 99%
“…CRC is one of the common malignancies in China, and results in high incidence and mortality 25 . Ferroptosis, a programmed cell death characterized by iron metabolism and ROS accumulation, was reported to be involved in the pathogenesis of many injury models, such as acute lung injury (ALI), 26 liver injury, 27 and neuronal injury 28 . In recent years, ferroptosis induction has been regarded as a promising therapeutic approach for various cancers, such as acute myeloid leukemia, 29 nasopharyngeal carcinoma, 30 gastric cancer, 31 and breast cancer 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Guan et al investigated the hepatotoxicity of 1,3-DCP and revealed its ability to induce ferroptosis in mouse liver cells. 79 Exposure to 1,3-DCP was shown to induce pathological changes, including the accumulation of iron and malondialdehyde (MDA), reduced GSH levels, and altered expression of ACSL4 and GPX4. Zhang et al investigated the effects of acrolein, a food and environmental pollutant associated with diabetes.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…Recently, emerging evidence has suggested that ferroptosis could play a role in VOC-induced toxicity. Guan et al investigated the hepatotoxicity of 1,3-DCP and revealed its ability to induce ferroptosis in mouse liver cells . Exposure to 1,3-DCP was shown to induce pathological changes, including the accumulation of iron and malondialdehyde (MDA), reduced GSH levels, and altered expression of ACSL4 and GPX4.…”
Section: Ferroptosis Inducers In Environmental Pollutantsmentioning
confidence: 99%
“…Solute carrier family 7 member 11 (SLC7A11) is a crucial subunit of the amino acid reverse transport system x c − , 28,29 and its silencing ultimately leads to GSH degradation and ferroptosis 20,21 . Furthermore, ferroptosis has been linked to increased levels of the two lipid peroxidation products malondialdehyde (MDA) 30 and 4‐hydroxynonenal (4HNE) 31 . Another pathway correlated with ferroptosis is the amplification of the esterification of arachidonoyl and adenosyl into PE by Acyl‐CoA synthetase long‐chain family member 4 (ACSL4) 32–34 .…”
Section: Introductionmentioning
confidence: 99%